Chapter Ricerca, teoria e prassi nella formazione adulta. Percorsi e prospettive di formazione adulta - DOZZA, Liliana (Studies on Adult Learning and Education, 2022)
The essay highlights the vast inherent power of education and research on education in and for adulthood - making use of the presentation and discussion of a Case Study -. This Case Study deals with the educational needs that is for the quality of the services of an elderly home in a City in northern Italy. The Case Study was conducted consistently with the theoretical-methodological framework of Grounded Theory and Participatory Research-Action. It allows us to capture "in nuce" some of the processes of generative and human change that can be shaped by clarifying the need/willingness to make improvements at the level of In-Service Training, School Training, and the elderly home organization. In sum, it emerges an awareness of the transformative value intrinsic in the "caring" professions. Lastly, the limitations of the research - conducted in COVID-19 time - and also the multiplicity of factors that triggered this beginning of change are considered, as well as the difficult implications of this work, given the dramatic challenges of the current socio-historical and geopolitical context.